Aplikasi Organ Tanaman sebagai Sumber Giberellin untuk Mengaktifkan Tunas Dorman Batang Nenas Bagian Tengah - Murniati '; Evawani '; Fetmi Silvina (Jurnal Sagu, 2007)
The research objective was to assay the plant organ extract that can be used to substitute synthetic gibberellins acid for activation of bud dorman of pineapple stem. This research was conducted by using completely randomized design with 4 treatment and 4 replication. The treatment were GA3. Kernel young maize, leave young maize and green beans germination. The result of experiment shows that the plant organ extract could be used as substitution GA3. Using the young leave of maize shows that producing time of seedling was faster, the seedling was 107,55% higher and 97,74% more weight than GA3 treatment.